Increase in Penicillin and multidrug resistance in Streptococcus pneumoniae (1993-2016): report from a tertiary care hospital laboratory, Pakistan - Afia Zafar; Lalani, Farida Khurram; Longi, Ahmer Arif; Jajja, Mohammad Raheel; Haider, Maera; Hashmi, Salila; Khan, Erum; Irfan, Seema; Hussain, Tabinda; Hussain, Faisal Riaz; Hasan, Rumina; Jabeen, Kauser (Journal of the Pakistan Medical Association, 2022)
Background: Streptococcus pneumoniae is a major cause of morbidity and mortality worldwide. With the emergence of penicillin-resistant S. pneumoniae (PRSP), treatment has become challenging. The Clinical and Laboratory Standards Institute (CLSI) in 2008 revised its guidelines for S. pneumoniae and recommended separate penicillin breakpoints for meningeal and non-meningeal strains. Similar to penicillin’s, resistance to other classes of antibiotics has emerged globally. Objective: The objective of this study is to determine the trend of resistance to antimicrobials in S. pneumoniae infections and the impact of new CLSI guidelines on penicillin susceptibility among meningeal isolates. Methodology: Twenty-four years (1993-2016) data from S. pneumoniae isolates and their antimicrobial susceptibility was retrieved from the computerized database. Data was divided into two groups for analysis, pre-2008 and post 2008. Results: Penicillin resistance remained unchanged in non-meningeal isolates during both study periods. A significant rise in penicillin resistance in meningeal isolates was observed in the second period 2008-2016 (2.9% vs 36.2%). High resistance rates were observed for co-trimoxazole, tetracycline and erythromycin. Increased trend of multi-drug resistant (MDR) strains were also noted, from 11% in 1999 to 36% in 2016. Conclusion: The emergence of MDR strains is evident from our dataset. It seems like the rise in PRSP in meningeal isolates is due to revised CLSI guidelines. Overall low resistance to penicillin in non-meningeal isolates and no resistance to ceftriaxone is encouraging and will assist in drafting local guidelines. Cautious use of antimicrobials are essential to reduce further emergence of antimicrobial resistance in indigenous isolates.